Global Engagement, Complex Tasks, and the Distribution of Occupational Employment - Carl Davidson; Fredrik Heyman; Steven Matusz; Fredrik Sjöholm; Susan Chun Zhu (Lund University, School of Economics and Management, Department of Economics, 2015)
Building on a framework introduced by Chaney and Ossa (2013), we construct a task-based model of the firm's choice of occupational inputs to examine how that choice varies with greater global engagement. We depart from Chaney and Ossa by assuming that more complex tasks are more costly to complete. Within the structure of our model, firms skew employment toward occupations engaged in more complex tasks. Moreover, the distribution of employment is more skewed for more globalized firms, while it is less skewed for larger firms. These results are consistent with our empirical findings in Davidson, et al (2015).
Keywords: F10; F16; F66; 330; Globalization; Firms; Tasks; Employment